AN EMPIRICAL STUDY OF THE IMPACTS OF PERCEIVED SECURITY AND KNOWLEDGE ON CONTINUOUS INTENTION TO USE MOBILE FINTECH PAYMENT SERVICES - Muhammad Ibrahim; Dr Muhammad Khalid Sohail; Ahmed Bilal Siddiqui (International Journal of Contemporary Issues in Social Sciences, 2024)
Financial technology (Fintech) are becoming one of the most prevalent services in today’s emerging technologies i.e., Internet of Things (IoT). The mobile payment sector is experiencing recent proliferation is also due to fintech payment services. From consumers perspective, one of the fastest growing fintech payment services are Apple Pay and Google Pay. Around the world different businesses are making full efforts to expand the usage of these services but the main concern is the security in its diffusion. The role of perceived security is of immense importance in mobile usage and unfortunately no in-depth investigation has been done so far for Fintech services. Thus, this research is determining the associations among variables like perceived security (PS), services knowledge (KNOW), confirmation (CON), perceived usefulness (US), continuous intention (CI) and satisfaction (SES). In context to Fintech services, the study as a theoretical model proposes extended post-acceptance model (EPAM). The proposed model data is collected from the service users and then validate on PLS. The results obtained from the test indicates the significant influence of knowledge and perceived security on the users confirmation and the perceived usefulness. Anyhow, there is no direct relationship found in perceived security on the users satisfaction and continual intention to use the Fintech services. The research further gives a significant relationship among confirmation, perceived usefulness, continual intention and satisfaction in terms o service usage. The practical and theocratical implications of this study have been discussed in detail.